Effective Methods for Managing the Innovative Potential of Enterprises - Bekmurodovich, Khosilov Shavkat (American Journal of Economics and Business Management, 2023)
The essence of the innovative potential of the staff as an innovative asset of the organization is concentrated in the unique knowledge and competencies of employees and is reflected in the models of innovative behavior that support the goals of the organization's development initiatives. These elements were identified through an analysis of the best practices of leading companies that develop HRD systems as structures for the development and support of innovative behavior of personnel.